A CASE STUDY OF THE SEATING ARRANGEMENT OF THE EIGHTH GRADE STUDENTS - Astuti, Kadek Wedi; Suarnajaya, I Wayan; Suputra, Putu Eka Dambayana (International Journal of Language and Literature, 2020)
This research aimed at observing the set-up of the seating arrangement during the instructions and identifying the students' reasons for having seating preferences. This study was conducted in SMP Negeri 1 Banjar, and the subjects were 32 students in 8F class. Two methods were applied in this study, namely observation and interview. Therefore, observation checklist and interview guide were used as the instruments. The results revealed that the set-up of the seating arrangement supported them in terms of comfort, flexibility in doing activities, doing tasks, spaciousness, and collaboration with the students. Meanwhile, it did not support them in terms of concentration, participation in class discussion, and collaboration with the teacher. Regarding their reasons for having particular seats, there were 14 reasons mentioned during the interview. Best friends and leaning on the wall were the factors that had the most and the least effect on the students in choosing their seats.